The Influence of Product Packaging and Brand Awareness on Repurchase Intention of Sumbawa Forest Massage Oil Mediated by Consumer Satisfaction - Yasmin Liana Izati; Lalu Adi Permadi (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of product packaging, brand awareness on repurchase intention of Sumbawa Forest Massage Oil with consumer satisfaction as a mediating variable. This study uses a quantitative approach with a correlational research design. Data collection was carried out through a Likert-scale questionnaire distributed online to 200 respondents who knew and had purchased Sumbawa Forest Massage Oil at least once, selected using a non-probability purposive sampling technique. The variables studied included product packaging, brand awareness, repurchase intention, and consumer satisfaction. Data analysis was carried out using Partial Least Square-Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4 through evaluation of measurement models and structural models. The results showed that product packaging and brand awareness had a positive and significant effect on consumer satisfaction, brand awareness and consumer satisfaction had a positive and significant effect on repurchase intention, while product packaging had no effect and was not significant on repurchase intention, but consumer satisfaction was proven to be able to mediate the influence of product packaging and brand awareness on repurchase intention. This study shows that increasing brand awareness and consumer satisfaction is the main strategy in encouraging repeat purchases and sustainability of traditional medicinal product MSMEs, and provides a basis for policy making and further research development by adding other variables or expanding the study object to other traditional herbal products.